Can higher education admission be more equitable? Evidence supporting the inclusion of relative ranking in the process. Issue 1 (1st January 2021) - Mardones, Juan Gallegos; Campos-Requena, Nelyda
Abstract: Many higher education systems require students to take admission exams, which are considered good predictors of academic performance. However, in Latin America, their use has been criticised for promoting socioeconomic segregation and favouring students of higher socioeconomic levels. This research complements the higher education admission process by using alternative measures of relative performance that promote greater equity in the system and allow access to higher education for more vulnerable sectors. A longitudinal study of students in Chile taking the University Selection Test (P.S.U.) and estimations of ordinary least squares (O.L.S.) in two stages were conducted. We found that the use of new measures of performance allows those more vulnerable students from public schools to reach equal and/or superior levels of relative performance than their peers from private schools. The practical implications of this research relate to recognising that good students can also attend public schools and that those students who have the capability can enter higher education, independent of their economic situations.